2012
DOI: 10.1007/s12094-012-0782-6
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer chemotherapy decisions in older patients: the role of patient preference and interactions with physicians

Abstract: Elderly lung cancer patients want to be involved in the decision-making process. Survival was the main treatment objective for more than half of the patients in this study. We have not found other published studies about elderly lung cancer patients' decisions about chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 32 publications
2
38
0
1
Order By: Relevance
“…To some extent, this finding probably reflects concern about toxicity in patients with comorbidity. Among patients with lung cancer, Gironés et al123 recently showed that withholding treatment was associated with factors such as poor health, advanced age, depression, and dementia, but not related to symptoms at diagnosis or cancer stage.…”
Section: Resultsmentioning
confidence: 99%
“…To some extent, this finding probably reflects concern about toxicity in patients with comorbidity. Among patients with lung cancer, Gironés et al123 recently showed that withholding treatment was associated with factors such as poor health, advanced age, depression, and dementia, but not related to symptoms at diagnosis or cancer stage.…”
Section: Resultsmentioning
confidence: 99%
“…Possible confounding factors for treatment (physician bias) have been prevented. [39] The number of cases was relatively high. To date, most studies of elderly lung cancer patients have been from subgroup analysis of phase III studies or were specific studies for elderly patients with fewer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies (Cuffe et al, 2012;Girones et al, 2012;Grose, Devereux & Milroy, 2011;Haasbeek et al, 2012;Landrum et al, 2012;Ngeow et al, 2010;Stevens, Stevens, Kolbe, & Cox, 2008;Vinod et al, 2008;Wang et al, 2012) relate to this gap. UK guidelines note that age alone should not exclude a patient from surgery as good outcomes have been reported for some older patients .…”
Section: Gap 4: Older Age and Co-morbidities Influence The Use Of Tmentioning
confidence: 99%
“…Interactions between age, comorbid conditions and performance status are complex; the incidence of comorbidities increases with age and rates of comorbidity are reported as double for lung cancer patients than for the general population (Vinod, Sidhom, Gabriel, et al, 2010). Other possible factors behind variations in treatment utilisation for the elderly and those with comorbid conditions include poor performance status, patient preference and refusal of treatment (Cuffe et al, 2012;Girones et al, 2012;Landrum et al, 2012;Ng et al, 2005;Vinod, Sidhom, Gabriel, et al, 2010). It has been argued that age and comorbidities should not deter clinicians from prescribing chemotherapy in preference to no active treatment (Ngeow et al, 2010).…”
Section: Variations In Treatments Offeredmentioning
confidence: 99%